Carbon-based artificial SEI layers for aqueous lithium-ion battery anodes. Issue 2 (2nd January 2020) - Subramanya, Usha; Chua, Charleston; He Leong, Victor Gin; Robinson, Ryan; Cruz Cabiltes, Gwenlyn Angel; Singh, Prakirti; Yip, Bonnie; Bokare, Anuja; Erogbogbo, Folarin; Oh, Dahyun
Abstract : Artificial SEI layers passing lithium ions but blocking water molecules for long-lasting aqueous lithium-ion batteries. Abstract : Replacing flammable organic electrolytes with aqueous electrolytes in lithium-ion batteries (LIB) can greatly enhance the safety of next-generation energy storage systems. With the extended electrochemical stability window of electrolytes, 'water-in-salt' (WIS) electrolytes containing LIB presented significant performance improvements. However, the solubility limits of lithium salts in water restrain the extent of kinetic protection offered by the high salt concentration. Here, we report design strategies of anode structure to improve the cycle life of LIB with WIS electrolytes. We introduced partially graphitic protective carbon layers on anode particles using a versatile coating method. This protective layer not only improved charge transfer kinetics but also minimized the exposure of anode surface for water electrolysis. The effectiveness of anode structure developed in this study was exemplified on TiO2 anodes, where cycle performance and coulombic efficiency improved by 11 times and 29% respectively over the base anode material.